2022
DOI: 10.3389/fpsyg.2022.902630
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Classic Chinese Garden Soundscape With Focus on Physiological and Psychological Effects, Tested Through Eye-Tracking, and Subjective Evaluation

Abstract: Soundscape has been valued and practiced in classical Chinese garden designs. Some authentic patterns were even mentioned and used in gardening books hundreds of years ago. Though these patterns are well-known, how they work in a classic Chinese garden is still unclear. In this study, we chose one of the most famous soundscapes called Tingyuxuan (Listening to the Sound of Rain Hall) in Zhuozhengyuan (Humble Administrator’s Garden), Suzhou as the object. A video of the Tingyuxuan was captured on a rainy day, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A previous study indicated that saccadic movements take 20-50 ms, while xations last for approximately 200 ms when reading text and longer when looking at images (19). Moreover, previous studies have focused on the relationship between visual attention to scenery and de ned xations as reaching approximately 200 ms (15)(16)(17)20). Thus, the eye xation duration was identi ed as being of at least 200 ms.…”
Section: Eye Movementmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study indicated that saccadic movements take 20-50 ms, while xations last for approximately 200 ms when reading text and longer when looking at images (19). Moreover, previous studies have focused on the relationship between visual attention to scenery and de ned xations as reaching approximately 200 ms (15)(16)(17)20). Thus, the eye xation duration was identi ed as being of at least 200 ms.…”
Section: Eye Movementmentioning
confidence: 99%
“…Simultaneously, the examiner asked participants to open their eyes and view the scene freely. According to previous studies, Eye movements were recorded for 60s (15,16,20,35). The participants were asked to close their eyes again.…”
Section: Experiments Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang studied the perception of soundscapes in national parks and their impact on visual aesthetics [15]. Sun, Minkai and Marafa [16,17] did pioneering work in the field of soundscape research in classical Chinese gardens, exploring the creation of soundscapes within classical Chinese gardens from the perspective of sound sources. Li [18] built a sound landscape assessment model for urban public open spaces.…”
Section: Urban Forest Park Acoustic Environment Studymentioning
confidence: 99%